Repercussions of lockdown on primary health care in India during COVID 19 - Shaili Vyas; Neha Sharma; Archisman; Pritam Roy; Raman Kumar (Journal of Family Medicine and Primary Care, 2021)
Primary health care is a comprehensive care with a wide range of essential services for people living in the rural and hard-to-reach areas. However, the primary healthcare delivery system in India is still in its initial stages and lacks human resources. With the COVID-19 pandemic around the corner, there has been a diversion of resources for controlling corona pandemic leading to undermining availability and accessibility of health services. This article highlights a few case scenarios and the multidimensional impact of lockdown on primary healthcare services. The article suggests certain appropriate measures that can be implemented as the lockdown simply cannot stop the transmission with no definite treatment and vaccine. There should be a multipronged strategy for breaking the chain of transmission and for future preparedness in case of such situations and to strengthen our primary healthcare system.